2008
DOI: 10.3354/ame01216
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relationship between active bacterioplankton and phytoplankton in the Southern Ocean

Abstract: Bacterioplankton are a heterogenous community composed of cells with different physiological states. The consideration of the active fraction of bacterioplankton as a potential factor affecting the strength of the relationship between bacteria and phytoplankton in the Southern Ocean was evaluated in waters around the Antarctic Peninsula. We estimated active bacterioplankton from uptake of 3 H-Leucine (bacterial production [BP]) and using vital stains to estimate their proportion within the total bacterioplankt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
21
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 42 publications
6
21
2
Order By: Relevance
“…In the Southern Ocean, Ortega-Retuerta et al (2008), in line with our finding, observed that LNA cells were more closely related to BP than HNA cells. In the present study, HNA and LNA subpopulations were likely governed by different forcings.…”
Section: Patterns Of Bacterial Abundances and Productionsupporting
confidence: 81%
“…In the Southern Ocean, Ortega-Retuerta et al (2008), in line with our finding, observed that LNA cells were more closely related to BP than HNA cells. In the present study, HNA and LNA subpopulations were likely governed by different forcings.…”
Section: Patterns Of Bacterial Abundances and Productionsupporting
confidence: 81%
“…Extrapolation of our rates to field conditions predicts a CDOM duplication time of 31-33 d, considering average BP values in the Antarctic Peninsula area during austral summer (Ortega-Retuerta et al 2008). However, in areas where high BP values were reported (e.g., in the western Weddell Sea during ice-free periods, where BP can reach 0.111 mg C h 21 L 21 ), CDOM duplication times of about 10 d are possible.…”
Section: Discussionmentioning
confidence: 99%
“…We forced the regression line to pass through the origin to avoid the effects of a high-CDOM background. To extrapolate these experimental rates to field CDOM bacterial generation rates (m 21 d 21 ), we used a mean BA of 7.14 3 10 5 cells mL 21 and a mean BP of 0.031 mg C L 21 h 21 ; these values were based on sampling and experimentation in the same area determined during the cruise ICEPOS 2005 (Ortega-Retuerta et al 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Water subsamples of 4 and 10 ml were filtered through 0.2 µm polycarbonate black filters and stained with DAPI (4, 6-diamino-2 phenylindole) to a final concentration of 1 µg ml −1 . During the cruises, BA was determined by flow cytometry by FACSCalibur Flow Cytometer (Beckton Dickinson©) as described in Ortega-Retuerta et al (2008).…”
Section: Methodsmentioning
confidence: 99%